Histologycally Confirmed Synchronous Pancreatic and Duodenal Double Cancer - E. S. Yelshibayeva; R. U. Kapi; D. Mardenkyzy; S. K. Gadylkan; M. M. Khoyshibay; A. N. Sapkina (Вестник рентгенологии и радиологии)
Pancreatic adenocarcinoma is the most pervasive form of cancer with high mortality rates. Being obscure at the early stages, non-specific symptoms and their onset only in the late stages of the disease lead to detection of the III–IV stages cancer on initial diagnistics. Gastrointestinal stromal tumor (GIST) is an intramucosal tumor of gastrointestinal tract, which is a derivate of interstitial cells of Cajal. The unicity of the presented clinical case is the rareness of GIST, which was an incidental finding during diagnostics of pancreatic adenocarcinoma. Diagnosed by intravenous contrast computed tomography, synchronous pancreatic and duodenal double cancer was confirmed histologically after Whipple surgery. The opportunities of intravenous contrast computed tomography in diagnostics of synchronous cancer were demonstrated.